2015
DOI: 10.1088/0953-4075/48/9/094011
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of propagation and energy deposition in femtosecond filamentation to the nonlinear refractive index

Abstract: The axial dependence of femtosecond filamentation in air is measured under conditions of varying laser pulsewidth, energy, and focusing f-number.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 45 publications
(130 reference statements)
3
20
0
Order By: Relevance
“…For comparison, simulations performed with a 100 fs laser pulse of comparable peak intensity, the contribution to plasma density from avalanche multiplication amounts to 3-5 %. We have also calculated that the losses due to molecular rotation only amount to 5.5% of total losses in our case, while it can exceed 50% in the case of 130 fs pulse at 800 nm [12]. The use of the long pulse duration strongly decreases the losses due to Raman Effect.…”
Section: Simulationsmentioning
confidence: 55%
See 2 more Smart Citations
“…For comparison, simulations performed with a 100 fs laser pulse of comparable peak intensity, the contribution to plasma density from avalanche multiplication amounts to 3-5 %. We have also calculated that the losses due to molecular rotation only amount to 5.5% of total losses in our case, while it can exceed 50% in the case of 130 fs pulse at 800 nm [12]. The use of the long pulse duration strongly decreases the losses due to Raman Effect.…”
Section: Simulationsmentioning
confidence: 55%
“…The pulse duration seems to have a stronger influence on the energy losses. By decreasing the pulse duration to 100 fs, Raman absorption becomes significant (as observed in [12,25]) and multiphoton ionization is strongly increased. The total energy losses are then raised to 20%.…”
Section: Comparison With Experimental Results and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…To demonstrate STOV generation in the arrest of self-focusing collapse, we perform simulations using Eq. (1), assuming azimuthal symmetry, and include electronic, rotational, and ionization nonlinearities in { } V ψ (18,20). The Gaussian input pulse is 3 mJ, 45 fs (Gaussian FWHM), with input waist w 0 =1mm.…”
Section: Spatio-temporal Optical Vortices (Stovs)mentioning
confidence: 99%
“…We recently showed that in the near-infrared (pump wavelength e = 0.8 µm), air propagation simulations depend very sensitively on the values used for the coefficients (n2) describing the instantaneous electronic nonlinear response of air constituents [18]. Best agreement of the simulations with axially resolved measurements occurs for n2 coefficients measured in [19].…”
mentioning
confidence: 99%